2000
DOI: 10.1159/000006640
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species and Intraspecies Morphometric Analysis of the Corpus Callosum

Abstract: A cross-species morphometric study of the corpus callosum was performed in the rat, rabbit, cat, dog, horse, cow and human. Across species, the results indicate a strong, although less than linear, dependency of callosal size on brain weight. This relation tends to lose significance within species. This is consistent with other morphometric studies indicating a tendency to decrease the correlations between morphometric variables in within-species analyses as compared to between-species analyses. There are spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
(48 reference statements)
8
35
0
Order By: Relevance
“…54). This notion is consistent with observations that the thickest callosal fibers, those serving primary and unimodal areas, scale with brain size across species, but the thinnest ones, those serving association areas, do not (55). Moreover, a recent clinical study found that homotopic functional connections are disrupted across a wide range of psychiatric conditions, including attention deficit hyperactivity disorder, major depression, and schizophrenia (56), raising the possibility that homotopic coherence may be a universal attribute of healthy brain function.…”
Section: Discussionsupporting
confidence: 91%
“…54). This notion is consistent with observations that the thickest callosal fibers, those serving primary and unimodal areas, scale with brain size across species, but the thinnest ones, those serving association areas, do not (55). Moreover, a recent clinical study found that homotopic functional connections are disrupted across a wide range of psychiatric conditions, including attention deficit hyperactivity disorder, major depression, and schizophrenia (56), raising the possibility that homotopic coherence may be a universal attribute of healthy brain function.…”
Section: Discussionsupporting
confidence: 91%
“…There is only a small contingent of fibers of very wide diameter whose caliber increases with increasing brain weight, but their increase in maximal diameter may not be sufficient to fully compensate for the increasingly long interhemispheric distances (10). Furthermore, across species the proportion of callosal fibers in relation to brain size or to the estimated numbers of cortical cells tends to decrease with increasing brain weight (10,51,52), thereby reducing the degree of interhemispheric connectivity. Overall, this evidence suggests that reduced callosal transmission is related to increased brain size, which is consistent with the hypothesis of Ringo et al (48).…”
Section: Relation To Brain Lateralizationmentioning
confidence: 99%
“…Combining our results and the data by Haug [1987], the exponential relation between callosal fibers (larger than 0.1 µm) and cortical cells should be about two thirds across species. This suggests that the proportion of callosal-projecting cells decreases in larger brains, perhaps contributing to an impairment of interhemispheric communication [Olivares et al, 2000], and producing an additional mechanism for hemispheric isolation besides interhemispheric transmission delay [Ringo et al, 1994].…”
Section: Fiber Number and Callosal/brain Sizementioning
confidence: 99%
“…One goal of the paper is therefore to test the concept that across species interhemispheric transmission time depends on brain size. We have chosen the callosal splenium (posterior fifth) because this structure has been the subject of previous studies [Swadlow et al, 1980;Kim et al, 1996;Kim and Juraska, 1997], is known to be involved in sensory transfer, especially visual [Hamilton, 1982;Pandya and Seltzer, 1986], and recent evidence suggests that there are species differences in this region relative to visual capacities [Olivares et al, 2000].…”
Section: Introductionmentioning
confidence: 99%